Investigation of influence of voltage source type on harmonic characteristics - Risnidar, Chan Bahaudin; Ismail, Daut, Prof. Dr.; Surya, Hardi Amrin; N., Hashim; Indra, Nisja; Syafruddin, Hasan (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/